The actual use of the deferential pedagogy and its role on to reach physical activities and sports aims on the skillful and knowledgeable levels during physical activities and sport. - Aggoun , hemza; sami , abdlakader; temar, mohamed (sports creativity, 2025)
The aim of this study is to know the effectiveness of deferential pedagogy to achieve the aims of physical activities and sport on the skillful and knowledgeable levels, and how it is used by teachers. 48 teachers of physical education from Ain Defla have participated in this study, and 22 students from Ahmed Allilli high school Ain Defla. The researcher has divided the search into two gates the first one is the theorical which includes the introductive side ,. while the practical side consists of researches' procedures and the analyses and discussions of the deduction outcome. the researcher has based in his search on a questionnaire that consists three units related to pedagogical uses, added to that there are special examinations related to the skillful and knowledgeable level . the researcher has already reached to a deduction in which all teachers of lycee must use widely the different pedagogy. since this pedagogy helps to realize the aims of physical and sport on the skillful and knowledgeable level